2020
DOI: 10.1016/j.jbusres.2019.01.061
|View full text |Cite
|
Sign up to set email alerts
|

Inferring attribute non-attendance using eye tracking in choice-based conjoint analysis

Abstract: Traditionally, the choice-based conjoint analysis relies on the assumption of rational decision makers that use all available information. However, several studies suggest that people ignore some information when making choices. In this paper, we build upon recent developments in the choice literature and employ a latent class model that simultaneously allows for attribute non-attendance (ANA) and preference heterogeneity. In addition, we relate visual attention derived from eye tracking to the probability of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 57 publications
0
8
0
Order By: Relevance
“…Most other studies (e.g. Balcombe et al, 2015;Yegoryan et al, 2018) suggest that visual attention based on eye tracking is not distributed equally across attributes. Balcombe et al (2015) showed that next to the last (monetary) attribute, the first and the last non-monetary attributes have the highest visual ANA.…”
Section: Attribute Non-attendancementioning
confidence: 97%
“…Most other studies (e.g. Balcombe et al, 2015;Yegoryan et al, 2018) suggest that visual attention based on eye tracking is not distributed equally across attributes. Balcombe et al (2015) showed that next to the last (monetary) attribute, the first and the last non-monetary attributes have the highest visual ANA.…”
Section: Attribute Non-attendancementioning
confidence: 97%
“…The experiment focused on unemployment support, a salient political issue in the countries. This should increase the likelihood that respondents consider the topic plausible and relevant, an important precondition to satisfy the assumption that decision makers in conjoint analysis use the information provided (Yegoryan, Guhl, and Klapper 2018).…”
Section: Empirical Approachmentioning
confidence: 99%
“…The experiment focused on unemployment support, a salient political issue in the countries. This should increase the likelihood that respondents consider the topic plausible and relevant, an important precondition to satisfy the assumption that decision makers in conjoint analysis use the information provided (Yegoryan, Guhl, and Klapper 2018). I then analyzed the data using ordinary least square regressions with cluster-robust standard errors because each respondent evaluated four pairs of unemployed individuals.…”
Section: Empirical Approachmentioning
confidence: 99%
“…Since choosing a preferred product profile (from a set of alternative offers) is an everyday occurrence for consumers, the Choice Based Conjoint (CBC) approach is attributed to represent a real-life purchase situation more realistically than traditional rating- or ranking-based conjoint approaches (Papies et al, 2011; Toubia et al, 2004). Accordingly, the ability of CBC to identify consumer preferences is widely recognized in marketing research (Hauser et al, 2019; Hennig-Thurau et al, 2007; Meyer et al, 2018; Yegoryan et al, 2020). Moreover, the given context of pricing research as well as the small number of product attributes considered in the study design argued for preferring CBC to alternative methods.…”
Section: Research Design and Empirical Findingsmentioning
confidence: 99%